Recent Progresses in Stable Isotope Analysis of Cellulose Extracted from Tree Rings - Silviu-Laurentiu Badea; Oana Romina Botoran; Roxana Elena Ionete (Plants, 2021)
In this work, the challenges and progression in stable isotope investigation, from the analytical tools and technical sample preparation procedures to the dendroclimatological experiments, were reviewed in terms of their use to assess tree physiological responses to environmental changes. Since the isotope signature of whole wood is not always a reliable tool in studying the climate changes, cellulose is often preferred as the study material in paleoclimatic studies. Nevertheless, the isotope analysis of cellulose is challenging due to the difficulty to remove the other wood components (extractives, lignin, pectin, and hemicelluloses). Additionally, in the case of hydrogen isotope analysis, about 30% of the hydrogen atoms of cellulose are exchanged with the surrounding water, which complicates the isotope analysis. In recent years, more automated isotope analysis methods were developed based on high temperature pyrolysis of cellulose, followed by the chromatographic separation of H2 from CO and by their individual isotope analysis using isotope ratio mass spectrometry. When used to investigate climate factors, the combined isotope analysis δ13C and δ18O appears to be the most promising isotope tool. In contrast, the role of δ2H values is yet to be elucidated, together with the development of new methods for hydrogen isotope analysis.